NAVIGATING THE PUBLIC SPACES: A GENDERED ANALYSIS OF ACTIVE AGEING AMONG OLDER WOMEN (Proceedings of the World Conference on Women’s Studies, 2024)
Abstract: In the phase of rapid urbanisation and a global rise in the ageing population, creating public spaces conducive to the well-being of the elderly population has become a pressing global concern. This study undertakes a comprehensive examination of the experiences of older women as they navigate public spaces within the framework of active ageing. Through a gendered analysis, the study aims to illuminate the unique dynamics that shape the daily encounters of older women in the public realm. The literature review reveals a gap in research concerning the intersection of gender, active ageing, and public spaces. This study employs a qualitative approach, incorporating in-depth interviews and observations to capture the nuanced interplay between gender, ageing, and public spaces. The interviews offer a personal perspective, allowing older women to share their stories and challenges while navigating various public spaces. Observations conducted in diverse urban settings provide a contextual backdrop, offering a visual understanding of the physical and social factors influencing the active ageing experiences of older women. The study is divided into two parts: the first deals with the gendered dynamics of public spaces, while the second part incorporates the contribution of public spaces in the active ageing process for older women. The study found that the experiences of older women in navigating public spaces vary widely based on factors such as location, cultural context, and individual circumstances. The respondents experienced physical challenges, safety concerns, transportation issues, social isolation, ageism and gender stereotyping, lack of accommodation and financial constraints as they moved through public spaces. This study contributes to the ongoing discourse on active ageing by offering a gendered lens that enriches the understanding of older women’s complexities in navigating public spaces.
Keywords: active ageing; older women; public spaces; well-being; social isolation